Incorporating marine macrophytes in plant–soil feedbacks: Emerging evidence and opportunities to advance the field. (12th November 2020) - Piercey, Rebecca S.; Gribben, Paul E.; Hanley, Torrance C.; Moles, Angela T.; Hughes, A. Randall
Abstract: Plants can change the biotic and abiotic characteristics of soil, which can in turn affect the growth of plants. For example, changes in below‐ground microbial composition by one plant can affect the relative performance of a second plant, in turn affecting the outcome of plant–plant interactions, invasive species success, species abundance distributions, successional processes and plant community composition and diversity. The effects of plant–soil feedbacks on population, community and ecosystem processes in coastal and marine soft‐sediment systems have received relatively little attention, yet several recent examples offer compelling evidence for their importance. Marine soft‐sediment systems offer an ideal opportunity to test key theoretical predictions for when plant–soil feedbacks may contribute to species coexistence and influence community composition, including the role of phylogenetic distance and relatedness, the potential for intraspecific feedbacks, the importance of environmental context, the influence of climate change and the implications for ecosystem function. Synthesis . There is a documented disconnect between marine and terrestrial research that slows the advancement of generalisable theory. We suggest that bridging this gap in our understanding of plant–soil feedbacks may provide a unifying framework underlying plant community structure in both terrestrial and marine ecosystems. Abstract : There is a documented disconnect between marine and terrestrial research that slows the advancement of generalisable theory. We suggest that bridging this gap in our understanding of plant–soil feedbacks may provide a unifying framework underlying plant community structure in both terrestrial and marine ecosystems.